Evidence-Based Medicine as a New Paradigm of Teaching and Practicing Medicine - Huicho, Luis (1997)
A critical review is made of this new proposal for medicine practice and teaching. A brief introduction of the medical context is first outlined. The content of Evidence-Based Medicine is then described, emphasizing the best available external clinical evidence, the clinical expertise and the predicaments of patients. Applications of this movement in clinical medicine and public health are pointed out. Finally, its advantages and potential risks and limitations are discussed. Evidence-based medicine is a novel viewpoint proposing a healthy subversion in medicine. It promotes a rational scepticism of physicians when faced with a clinical problem. To make a clinical decision, they should not be satisfied with the advice of their venerable expert colleagues, they should instead turn their attention to the combination of external evidence, their own clinical expertise and the predicaments of their patients.